สารให้ความหวานแทนน้ำตาลเพื่อสุขภาพและการควบคุมน้ำหนัก - ธนวิยุทธ์ภัคดี, ปรัญรัชต์; ศรีอนุชาต, ทรงศักดิ์ (Thai Journal of Science and Technology, 2019)
Abstract Intense sweeteners are commonly used to substitute sugars (sucrose) in food and beverage products as a reason of providing sweet taste with low or no calorie. Currently, eight synthetic intense sweeteners (aspartame, cyclamate, saccharin, acesulfame potassium, sucralose, neotame, alitame and advantame) are approved as a safe sweetener in food, and three natural-based sweeteners (thaumatin, steviol glycosides, and Luo han guo extract or Monkfruit extract) are classified as generally recognized as safe and permitted for use in food by many countries. Owing to their low or no caloric intake and health benefits especially in the person who needs to reduce sugar intake, they are increasingly used as table-top and in many types of food products such as carbonated soft drink, instant cereals and sugar-free desserts which are recommended to use for weight loss. In each country, they have been controlled under specific regulation as GMP and with specific values along the types of food items. Obesity is a major global public health problem. It affects children and adults, and spans all ethnicities and races. Then, the sweeteners are being recommended as a choice for weight loss. However, the data from many studies indicated that the intended effects did not correlate with what was seen in clinical study. In practical, safe weight reduction is the time-consuming process by changing behavior and lifestyle with proper nutrition and physical activity. Keywords: intense sweeteners; health; weight reduction; energy; glycemic index; regulation